A Prospective Observational Study on Assessment of Etiology, Complications, and Stages of Renal Diseases in the Khammam District of Telangana - Sandhya, Patibandla Sai; Nikhil, Soma Mani Santhosh; Reddy, Phakkir Vineela; Niharika, Rekala; Chinnaeswaraiah, Maram (International Journal of Pharmaceutical Investigation, 2025)
Background Renal pathologies, encompassing Chronic Kidney Disease (CKD) and Acute Kidney Injury (AKI), represent considerable public health challenges, contributing to heightened morbidity and mortality rates on a global scale. In India, the increasing trends of urbanization, environmental determinants, and alterations in lifestyle have exacerbated the incidence of renal ailments. This research endeavor seeks to evaluate the underlying causes, associated complications, and progressive stages of renal diseases in the eastern districts of Telangana, where epidemiological data are notably scarce. Materials and Methods statistical analyses to assess disease patterns, complications, and treatment outcomes. Comorbidities, biochemical parameters, and treatment modalities were recorded. We performed 327 patients were enrolled, who were diagnosed on renal diseases. Demographics, medical history, centers of eastern Telangana. Based on the specified inclusion and exclusion criteria, a total of A prospective observational study was carried out in tertiary care. Results Renal disease prevalence reached its peak among people who fell within the age bracket of 55-64 years (25.99%) and these patients mostly identified as male (65.44%). The patient population concentrated heavily in rural settings where healthcare access problems could exist because 63.3% of patients came from those areas. The study revealed hypertension affected 70.33% of patients while diabetes mellitus developed in 29.66% of the participants. Patient evaluation demonstrated that stage 5 CKD affected 62.15% of cases while stage 4 affected 20.92% and stage 3 affected 14.15% of cases. Patients experienced three main complications: anemia affected 70.33% of patients followed by volume overload affecting 63.3% and sepsis developing in 12% of patients. Workplace interventions resulted in enhanced renal functionality because patients experienced serum creatinine level reduction from 5.56 to 3.21 mg/dL while their Glomerular Filtration Rate (GFR) increased from 17.08 to 48.4 mL/min. Conclusion This study highlights the substantial burden of renal diseases in the region, with hypertension and diabetes being the primary risk factors. The higher prevalence among rural populations emphasizes the need for improved healthcare access and early screening programs. Targeted interventions, enhanced patient education, and optimized management strategies are crucial to slowing disease progression and improving patient outcomes.
Keywords: Chronic kidney disease; Acute kidney injury; Telangana; Renal complications; Dialysis; Hypertension; Diabetes